Approximation by nonlinear Hermite-Fejer interpolation operators of max-product kind on Chebyshev nodes - Coroianu, Lucian; Gal, Sorin G. (Rev. Anal. Numér. Théor. Approx., 2010)
The aim of this note is that by using the so-called max-product method, to associate to the Hermite-Fejer polynomials based on the Chebyshev knots of first kind, a new interpolation operator for which a Jackson-type approximation order in terms of \(ω_1(f; 1/n)\) is obtained.